HUMANISASI ALLAH Dalam Permenungan Feuerbach - Valentinus . (Litbang STFT Widya Sasana Malang, 2009)
Negation or aggression to religious institutions belongs to the human civilization or history of humanity. Every where and every time there are men that don’t believe to God. But Feuerbach’s negation to God and aggression’s to religion were more different and radical than before. The difference and the radicality stay at systematic and profound analyses philosophically and convincing content doctrinally. In modern epoch, the aggression and the negation to God and religions are so rational and sophisticated. The pioneer of those kind attaches and refusals was Feuerbach, expressing in his concept about humanization of God.